Pendidikan Kesehatan Tentang Japanese Encephalitis Berpengaruh Pada Tingkat Pengetahuan Siswa Sekolah Dasar Di Canggu, Bali - Ni Made Ari Sukmandari (JURNAL MEDIKA USADA, 2019)
Japanese Encaphalitis (JE) is an inflammation of the brain caused by Japanese Encaphalitis virus and transmitted by JE virus mosquitoes requiring animals as intermediary hosts such as pigs and several bird species. Culex mosquitoes breed in places of standing water such as rice fields, ponds and biting, especially at night. In Bali, JE disease is increasing every year. Immunization is the most effective way to prevent JE in humans. In order to complete basic immunization and reduce child morbidity and mortality rates, starting in 2017 the government add 3 new vaccines, one of them is the JE vaccine. The government carried out a campaign and introduction of JE immunization which began in Bali province. The immunization campaign was scheduled for March-April 2018. In addition to JE immunization as one of the diseases prevention, it certainly cannot be separated from education and counseling as prevention of JE disease. This study aimed to find out the effect of health education about JE towards knowledge level of elementary school students in Canggu Village, Badung Regency. The research design was pre-experimental with one group pretest posttest design. Sampling was carried out using Wilcoxon test. The results of this study found that there was an effect of knowledge about JE before and after being given education.